2017
DOI: 10.1080/21580103.2017.1292958
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of native woody regeneration in exotic tree plantations and natural forest in Southern Philippines

Abstract: The use of exotic species in reforestations is one of the highly criticized forest policies in the Philippines, mainly due to their perceived negative impacts on biodiversity conservation. To ascertain the influence of exotic plantations on native flora establishments, we inventoried the structure, composition, and diversity of understory woody regeneration in three exotic stands in Southern Philippines and compared them to adjacent second growth forest. The mean total density of regeneration did not differ si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
3
4
0
Order By: Relevance
“…Thus, a low number of propagules (propagule pressure) would decrease the probability that this species can establish itself, persist, naturalize, spread, and invade (You et al ), unlike the invasion success that has been shown by some introduced plants that produce a greater number of propagules (Liu et al ). Similar results in the Southern Philippines led to the suggestion by Tulod et al () that some exotic tree plantations could support the regeneration of indigenous species, given the higher density of native saplings in the plantations compared to that in the natural forest.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Thus, a low number of propagules (propagule pressure) would decrease the probability that this species can establish itself, persist, naturalize, spread, and invade (You et al ), unlike the invasion success that has been shown by some introduced plants that produce a greater number of propagules (Liu et al ). Similar results in the Southern Philippines led to the suggestion by Tulod et al () that some exotic tree plantations could support the regeneration of indigenous species, given the higher density of native saplings in the plantations compared to that in the natural forest.…”
Section: Discussionsupporting
confidence: 75%
“…In fact, the impacts of invasions by conifer species, especially pine, have been widely recognized (Langdon et al ). It has been noted that, in addition to their difficult control, they could even interfere with restoration projects (Tulod et al ). For these reasons, the selection of fast‐growing exotic species for the establishment of plantations should be prudent (Rejmánek & Richardson ; Grotkopp et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In managed C. lusitanica plantation forest, mean seedlings regeneration strongly higher than all other plantation forest types and adjacent natural forest whereas unmanaged E. globules and C. lusitanica and managed E. globules not significantly differed seedling regeneration between them. This result also inline to the study of diversity of native woody regeneration in exotic tree plantations and natural forest in Southern Philippines (Tulod et al, 2017).…”
Section: Natural Regenerationsupporting
confidence: 78%
“…Forest plantations are relatively young anthropogenic ecosystems compared to natural forests, and with just one tree species they offer fewer habitats than a natural forest with a mixture of species, life forms, ages of trees and of dead wood. Plantations of exotic trees are known to suppress native vegetation (Braun & Vogt, 2014;Tulod, Casas, Marin, & Ejoc, 2017;Wijesinghe & de Silva, 2012).…”
Section: Resultsmentioning
confidence: 99%